Cents and sensibility what economics can learn from the humanities - Morson, Gary Saul 1948; Schapiro, Morton Owen (Princeton,New Jersey Princeton University Press, 2017)
Economists often act as if their methods explain all human behavior. But in Cents and Sensibility, an eminent literary critic and a leading economist make the case that the humanities, especially the study of literature, offer economists ways to make their models more realistic, their predictions more accurate, and their policies more effective and just. Gary Saul Morson and Morton Schapiro trace the connection between Adam Smith's great classic, The Wealth of Nations, and his less celebrated book on The Theory of Moral Sentiments, and contend that a few decades later Jane Austen invented her groundbreaking method of novelistic narration in order to give life to the empathy that Smith believed essential to humanity. Morson and Schapiro argue that Smith's heirs include Austen, Anton Chekhov, and Leo Tolstoy as well as John Maynard Keynes and Milton Friedman. Economists need a richer appreciation of behavior, ethics, culture, and narrative--all of which the great writers teach better than anyone. Cents and Sensibility demonstrates the benefits of a freewheeling dialogue between economics and the humanities by addressing a wide range of problems drawn from the economics of higher education, the economics of the family, and the development of poor nations. It offers new insights about everything from the manipulation of college rankings to why some countries grow faster than others. At the same time, the book shows how looking at real-world problems can revitalize the study of literature itself.
Spotting the spoof : the value of telling stories out of (and in) school -- A slow walk to judgment : hedgehogs and foxes, wisdom and prediction -- The power and limits of the economic approach : case study 1--how to improve American higher education -- Love is in the air...or at least in the error term : case study 2--what economists can and cannot teach us about the family -- The ultimate question : case study 3--why do some countries develop faster than others? : economics, culture, and institutions -- The best of the humanities -- De-hedgehogizing Adam Smith : the economics that might be -- Humanomics : a dialogue of disciplines.
Includes bibliographical references and index.
Keywords: Economics -- Moral and ethical aspects; Economics -- Psychological aspects; Business and economics -- General; Business and economics -- Education; Business and economics -- Decision-Making & Problem Solving